Analysis of Organizational Structure of Zila Panchayats - Kumar Garg, Dr. Vinay; Garg, Rashi (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Article 243 ZD of the Constitution of India inserted wide 74th Constitutional Amendment Act in 1993 which states that ‘There shall be constituted in every State at the district level a District Planning committee to consolidate the plans prepared by the Panchayats and the Municipalities in the district and to prepare a draft development plan for the district as a whole’. In line with the above amendment the government of Uttar Pradesh enacted the Uttar Pradesh District Planning Committee Act, 1999 (Act) through Act no. 32 of 1999 in July 1999. The Act provided that there shall be constituted a District Planning Committee (DPC) in each district to prepare District Development Plan (DDP) for whole of the district integrating the plans prepared by Panchayats and Urban Local Bodies(ULBs), and allocate funds to sectors and sub-sectors within outlines of the DDP. As sectors and sub-sectors for expenditure are operated in line/service departments, DPC was also to consider development plans of line/service departments. However, the Act did not provide for preparation and approval of annual plans of line departments clearly. The provided that the DPC will also assess the physical and natural resources available in the district and will prepare and approve integrated district development plan considering its judicious allocation amongst PRIs, ULBs and line departments keeping in view integrated development of the district and environmental protection. DPCs were required to meet at district headquarters at least once in three months on the date as decided by the President of the committee. Key words- Planning, Act, Government, Committee, resources.